Calcium carbonate (CaCO3), total organic carbon (TOC) contents and carbon-to-nitrogen ratio (C/N) from composite sediment core BIS-2000 - Stefan Lauterbach; Frank Harald Neumann; Rik Tjallingii; Achim Brauer (PANGAEA, 2024)
The data set bundle comprises geochemical, XRF core scanning and pollen data from composite sediment core BIS-2000, which was compiled from two parallel sediment cores (BIS-1 and BIS-3) obtained near Bispingen, northern Germany (53.071528°N, 9.989861°E, 82.0 m). BIS-2000 comprises Last Interglacial (Eemian) to early Last Glacial (Weichselian) palaeolake deposits, which cover the section between 15.55 and 30.68 m composite depth. The data set Bispingen BIS-2000 geochemistry contains calcium carbonate (CaCO3) and total organic carbon (TOC) contents (expressed as per cent of sediment dry weight) as well as carbon-to-nitrogen ratio (C/N) data. Analyses were carried out at the GFZ German Research Centre for Geosciences in Potsdam, Germany, on the section between 15.55 and 30.72 m composite depth. The CaCO3 content was calculated from the total inorganic carbon (TIC) content, which was measured using a STRÖHLEIN Coulomat 702. In addition, measurements of the total carbon (TC) and total nitrogen (TN) contents were carried out using a LECO CNS-2000 elemental analyser. TOC was calculated as the difference between TC and TIC and C/N was calculated as the mass ratio between TC and TN.